Intelligence as a service : designing semantic APIs to intelligent software - Köykkä, Markus (2011)
The purpose and focus of this Bachelor’s Thesis is to explore, examine and (to some extent) analyze the design heuristics and guidelines of an API that is to be implemented for a software or service that facilitates AI. An essential challenge in the creating of the thesis is that there are no papers to be found on the particular subject. General API design guidelines, related W3C recommendations and basic requirements of AI are explored, while trying to form some kind of a cohesion about what a semantic API for an intelligent software would or should be like.